Ideology Enforcement in Three Poems Chadur and Char-Diwari (2012) by Fahmida Riaz, Gracefully She Approached (2003) by Simin Behbahani, and Daughter of Afghanistan (2005) by Nadia Anjuman - Nurul Refsi Pangestu; Kurnia Ningsih (English Language and Literature, 2020)
The purpose of this analysis is to expose the issue of ideology enforcement in poems Chadur and Char-Diwari (CCD) by Fahmida Riaz, Gracefully She Approached (GSA) by Simin Behbahani, and Daughter of Afghanistan (DOA) by Nadia Anjuman. The issue of ideology enforcement refers to the patriarchy system strategies in applying their rules to the women. The problem of this analysis is to find how far these poems expose the issue of the patriarchy system's ideology enforcement. This analysis aims to expose men's rule influence toward the Pakistan, Iran, and Afghanistan women. This analysis uses the contribution of poetic elements; imagery, symbol, and diction in revealing the issue of the patriarchy system's ideology enforcement. The analysis is based on the concept of a feminist by Kate Millet, Naomi Wolf, and Betty Friedan that is supported by the text and context-based interpretation. The result of this analysis is the strategy of the patriarchy system enforcing their ideology toward the women. The men play their authority in the women's role and activity in public. The strategies are applied in two ways; manipulation and indoctrination.